"Danger Zones, " "Death Zones, " and Paradoxes of Infrastructural Space-Making in Manila. Issue 1 (2nd January 2022) - Saguin, Kristian Karlo; Alvarez, Maria Khristine
ABSTRACT: Infrastructure and the spatial practices that coalesce around them come to matter in multiple ways. Building on the legacy of splintering urbanism and subsequent appraisals, we explore the paradoxes of infrastructural spaces in a Global South city. In Manila, urban infrastructure plays a central role in enabling evictions in city spaces marked as "danger zones, " and in inhabiting "death zones" in the peripheries where evictees are resettled. This piece employs a relational view of the tensions between the dispossessive and sustaining work of infrastructure to extend the spatial metaphors of urban infrastructure and to illuminate political possibilities built around connections.